Zinc-α2-Glycoprotein Knockout Influenced Genes Expression Profile in Adipose Tissue and Decreased the Lipid Mobilizing After Dexamethasone Treatment in Mice - Zhang, Wenge; Qiao, Yu; Qi, Fulei; Shen, Qingyi; Zhao, Ruqian; Yang, Xiaojing (Hormone and Metabolic Research, 2020)
Zinc-α2-glycoprotein (ZAG), as an adipokine, plays an important role in lipid metabolism. However, its influence on whole gene expression profile in adipose tissue is not known. Under stress condition, how ZAG affects the lipid metabolism is also unclear. Therefore, in this study ZAG systemic knockout (KO) mice were used as a model to reveal the genes expression profile in visceral fat tissues of ZAG KO mice and wild-type mice by genome-wide microarray screening. Then dexamethasone (DEX) was used to explore the effect of ZAG deletion on body fat metabolism under stress. Our results showed that 179 genes were differentially expressed more than 1.5 times between ZAG KO mice and wild type mice, of which 26 genes were upregulated dramatically and 153 genes were significantly downregulated. Under DEX simulated stress, ZAG systemic knockout in vivo resulted in a markedly decrease of triglycerides (TG) and nonesterified fatty acid (NEFA) content in in plasma. Similarly, for lipid catabolism, ZAG KO led to a significant increase of phosphorylated HSL (p-HSL) protein and a rising tendency of adipose triglyceride lipase (ATGL) protein relative to those of the DEX group. For lipid anabolism, fatty acid synthase (FAS) and adiponectin protein expression in visceral fat rose notably in ZAG KO mice after DEX treatment. In conclusion, ZAG knockout can affect the gene expression profile of adipose tissue, reduce elevated TG and NEFA levels in plasma, and alter lipid metabolism under DEX treatment. These findings provide new insights into the mechanism of lipid metabolic disorders in response to stress.
Keywords: ZAG; dexamethasone; lipometabolism; mice